Developing E-dictionary based on MIT App Inventor for Preschool Students - Mursyid, Abdillah; Stanley , Sakala (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2024)
Living in a technologically driven world, students are affected by the latest technological products since they have not been a student yet. Thus, as a teacher we are demanded to be wise and aware in selecting media to deliver our materials in teaching. We should understand that our students now are millennials and they use digital technology in their daily lives. This current study intended to develop E-Dictionary based on MIT App Invertor in teaching English vocabulary for preschool students. In developing the product this study adapted the R& D model from Borg and Gall. They are seven steps prosecuted in this present study: (1) Need analysis, (2) Media Development, (3) Expert Validation, (4) Revision, (5) try Out, (6) Second Revision, and the last (7) is Final Product. The final product was E-dictionary with supporting facilities such as the pictures, sounds, quizzes, reminders, etc. This project appears to help teachers convey English instructions in ease during the teaching learning process. The result suggest that E-dictionary developed impact positively to the teacher as well as the students.